The role of gastrostomy in the staged operation of esophageal atresia - Hosseini Seyed; Davani Sam; Sabet Babak; Forutan Hamid; Sharifian Maryam (Wolters Kluwer Medknow Publications, 2008)
Introduction: The aim of this study is to recommend criteria for selection of patients who benefited from the use of gastrostomy rather than emergency fistula closure during the staged operation of esophageal atresia (EA). Materials and Methods: Between August 2004 and July 2006, 75 cases of EA, were consecutively operated. Nineteen out of 75 (25%) underwent routine gastrostomy because they required a type of staged operation: Group I: Five cases with pure atresia had gastrostomy and esophagostomy; Group II: Six with severe pneumonia and congenital heart disease (Waterson class C) had gastrostomy and conservative management; Group III: Eight with long gap EA (2-4 vertebras); four out of 8 cases underwent primary anastomosis with tension and the other four had delayed primary anastomosis plus primary gastrostomy. Results: GI: Only three cases survived after esophageal substitution; GII: Three out of six cases with severe pneumonia (fistula size: f > 2.5 mm) underwent emergency fistula closure with only one survival, but all (f < 2.5 mm) recovered without complication, GIII: Four patients with long gap and primary anastomosis with tension developed anastomotic leakage; they required gastrostomy following the leakage, except for those with delayed primary anastomosis, and all of them recovered without early complications. Conclusion : All the cases with long gap, although two esophageal ends can be reached with tension, should undergo delayed primary closure with primary gastrostomy. Those were brought with Waterson class C and the fistula size greater than 2.5 mm should undergo emergency fistula closure; however, if fistula size was less than 2.5 mm, it is better to be delayed by primary gastrostomy for stabilization. In this study, we had a better outcome with gastric tube for substitution than colon interposition in infants.